International Mindedness and Intercultural Competence: Perceptions of Pakistani Higher Education Faculty - Zehra Habib (Journal of Education and Educational Development, 2020)
This qualitative study endeavored to examine higher education faculty members’ understanding of international mindedness and intercultural competence and sought their views on professional development programs competency in evolving an internationally minded stance. The focus of this study was on international mindedness because in the current era of globalization, it has become imperative to inculcate world mindedness in students and to prepare them for global citizenship. Data were collected through in-depth individual interviews held with eight faculty members teaching at two higher education institutions in Karachi, Pakistan. Dominant findings demonstrated that most participants had limited insight regarding the concepts and that these were applied minimally in their current teaching practices. Although, lauding an international minded approach, most participants considered understanding of local cultures more relevant before moving on to international visions. Participating faculty also reflected that there was lack of professional development and that for understanding local and international dynamics, specialized education programs were an important factor. The study concluded with implications for professional growth platforms to foster global mindedness in educators in order for them to promote international mindedness in students.
Keywords: global citizens, intercultural awareness, international mindedness, professional development education.